Innovative culture elements within the clothing trade in the Municipality of Maicao-Colombia - Quintero Ramos, Meudis Patricia (2018)
In this research the elements of the innovative culture that are implemented by clothing traders, located in the Maicao municipality in Colombia, are determined. These traders have reported an unexpected decrease in their sales, which has impacted the regional, national and international economy. This determination was based on the evaluation of five key elements derived from this culture, namely, encouraging the generation of new ideas, motivation of employees, transmission of knowledge and experiences, introduction of new technologies, and investing, risking and experimenting. This evaluation was carried out through a survey designed and applied to a sample of sixty-three (63) merchants in the area. The results showed that 39.6% of the sample almost never introduces new technologies and 30% never develops the activities that involve investing, risking and experimenting, both elements were located at a low and very low level, respectively within the categorization scale for the statistics of the variable. Consequently, it is concluded that the lack of implementation of these elements, typical of the innovation culture which characterizes the most competitive organizations at this time, represents one of the main causes that slow down the productive capacity of these traders, preventing the sales increasing in this bordering context.